Compact Optical Add-Drop De-Multiplexers with Cascaded Micro-Ring Resonators on SOI - 关欢 李智勇 亢海华 俞育德 (Chinese physics letters, 2017)
A four-channel integrated optical wavelength de-multiplexer is experimentally illustrated on a silicon-on-insulator （SO1） substrate. With the aid of cascaded micro-ring resonators, the whole performance of the wavelength de- multiplexer is improved, such as 3 dB bandwidth and channel crosstalk. Based on the transform matrix theory, a four-channel wavelength de-multiplexer with average channel spacing 4.5±0.5 nm （3 dB bandwidth - 2 ± 0.5 nm） is demonstrated at telecommunication bands. For each channel, the extinction at the adjacent channel is below -39dB and the out-of-band rejection ratio is up to 40dB. The channel dropping loss is below 5dB in the five FSR spectral response periods （near 100 nm）.